Politeness Strategies Employed by Lecturers in Undergraduate EFL Classroom - Septian Ardianto (Linguistic, English Education and Art (LEEA) Journal, 2023)
This study investigates the politeness strategies employed by lecturers in EFL undergraduate online classroom. This study focuses on answering a research question; (1) how do the strategies employed by the lecturers in their teaching-learning activity. The qualitative method was used to fulfil the objective of the study. The data was collected from sit-in observation during their teaching-learning process. It was transcribed and analysed descriptively. The result shows that there are three strategies that employed by the lecturers namely positive politeness, negative politeness and bald-on-record. It can be concluded that this study will enrich the discussion which relates to the used of politeness strategies in teaching-learning program and how this study helps other lecturers/teacher to enrich their view in conducting kinds of strategies in their teaching-learning activity. Keywords: EFL Undergraduate Classroom, Online Classroom, Politeness Strategies